Limited edition : prototypes, one-offs and design art furniture - Lovell, Sophie (Boston, MA : Birkhaeuser, 2009)
Prototypes -- One-Offs -- Edition X -- The New Patrons -- Auctions and Attitudes -- Contributors.
boek